Moral Values on Teachers’ Directive Speech Acts Through Arabic Teaching l al-Qiyam al Akhlaqiyyah fi al-Af’al al-Taujihiyyah Atsna’a Ta’lim Lughah al-Arabiyyah - Qomariyah, Lailatul; Ahya', Akhmad Sauqi; Adam Ibrahim, Faishol Mahmud (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
Moral value is vital and beneficial in students' lives. This value is utilized as a guide in behavior when interacting in Arabic learning activities. This value craves to be internalized in these activities through the teacher's acts with the aim that learning can run interactively and create character students. This study aims to analyze the internalization of character values through teacher directive acts in learning Arabic at Darus Salam High School and Al Munawaroh High School Jombang. This research adopted a qualitative approach by employing the case study. The research data was obtained from interviewing and documentation of three teachers’ directive speech acts from two senior high schools about the context of these teachers’ acts. This study draws on the internalization of character values through teacher directive acts in learning Arabic at Darus Salam and Al Munawaroh High School Jombang with four functions, they are; a) the function of asking, b) the function of ordering, c) the function of inviting, and d) the function of forbidding by internalizing character values, namely the value of curiosity, independent value, religious value, and responsibility value. The results of this study contribute to the teacher's media in using appropriate speech acts as an effort to create students who have character and become more interactive and communicative learning because of the understanding between teachers and students. The implications for future research need to discuss the following research to understand character values through Arabic teaching materials.